2000
DOI: 10.1002/(sici)1099-1085(20000430)14:6<1119::aid-hyp8>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Development of a portable field rainfall simulator for use in hillside vineyard runoff and erosion studies

Abstract: Abstract:An inexpensive, mobile ®eld rainfall simulator and runo plot frame were developed for use on hillside vineyards. The simulator framework and components were lightweight, readily available and easily manageable such that they can be handled by one person during transport, set±up and operation. The vineyard rainfall simulator was simpler than many of the machines in recent use for similar studies, yet oered equal or improved performance for small-plot studies. The system developed consistent sized 2 . 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 16 publications
(23 reference statements)
0
23
0
1
Order By: Relevance
“…Drop forming rainfall simulators were designed and calibrated to specifications outlined by Battany and Grismer (11). Surface runoff from simulations was collected as volume intervals and time recorded for calculation of runoff rate (see the supporting information section for more detail on this and other aspects of the experimental procedures).…”
Section: Methodsmentioning
confidence: 99%
“…Drop forming rainfall simulators were designed and calibrated to specifications outlined by Battany and Grismer (11). Surface runoff from simulations was collected as volume intervals and time recorded for calculation of runoff rate (see the supporting information section for more detail on this and other aspects of the experimental procedures).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial distribution of the rainfall intensity was tested by taking measurements of the rain amount at 15 points using small plastic cups over the 2 m 2 plot area. The collected rain amount data were then used in the Christiansen uniformity formula (Abudi et al, 2012;Battany and Grismer, 2000). The spatial distribution of the rainfall intensity over the study area is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on rainfall simulators is extensive; for a more complete review see Battany and Grismer (2000). The standard small-or laboratory-scale (1 m 2 or smaller) rainfall simulator is a drip tank (Cerdà et al, 1997;Foster et al, 2000;Fernandez-Galvez et al, 2008, and many others).…”
Section: T G Wilson Et Al: Plot-scale Rainfall Simulation and Paramentioning
confidence: 99%